STRATEGI PEMASARAN HOTEL SANUR PARADISE PLAZA UNTUK MENINGKATKAN PENJUALAN KAMAR MELALUI PAKET RESIDENTIAL MEETING - ., Santoso; Reja Arjana, I Ketut (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2011)
MICE (Meeting, Incentive, Conference and Exhibition) is growing up rapidly in Indonesia, especially in Bali. MICE participants are on a line with other tourists who also need accommodation and recreation. This condition makes Sanur Paradise Plaza Hotel provides Residential Meeting Package to accommodate MICE activities. In order to find out the factors of unreachable Room Selling Volume, research was conducted to I 00 respondents. The data were analyzed by Variance Analysis and Comparative Descriptive Analysis based on the Theory of Marketing Mix. The result shows that the quality of meeting room and its price are not compatible with consumers expectation. Suggestions for the hotel is to make new variation of Residential Meeting Package, such as: adding Spa Service and renovate the Meeting Room physical condition. The price needs to be adjustable with market condition, giving special rate for some certain moments to attract customers. Promotion should be more optimized in order to give information about meeting package by improving partnership with travel agent and event organizer.